Empowerment of Pokdakan in the Context of Increasing Tilapia Fish Production Using the Biofloc System in Anreapi Village, Polewali Mandaí Regency - dahniar, dahniar; Jamal, Abd; Fajrian, Fajrian; Ali, Najmah (Abdi Masyarakat, 2024)
The aim of this PKM activity is to increase the productivity of tilapia cultivation using the biofloc technique so that harvest and marketing results increase to increase the optimal income of partner group members. The final target to be achieved in this activity is to improve partners' skills in sustainable production and marketing of tilapia. The implementation methods for this activity to overcome partner problems are socialization, training, application of technology, mentoring and evaluation, and program sustainability. The results of this service are carried out in the form of training and guidance on the application of biofloc technology. To measure the level of knowledge of participants during this activity, a pre-test and post-test were carried out regarding biofloc technology and online marketing. The results obtained by partners' knowledge about biofloc technology were on average 93.79% of those who did not know, 6.21% of those who already knew. After implementation there was an increase of 80.55% who knew and 19.45% who didn't know. In the marketing aspect, before the training was carried out, the level of partner knowledge was 82.23% who did not know and 17.77% who knew. After implementation, there was an increase in the level of knowledge of partners from 82.23% who did not know to 98.00% who knew about marketing on social media. From the results above in terms of productivity carried out by group members, it is hoped that it can increase production both in terms of quantity and quality of tilapia. , while the marketing aspect can provide insight and understanding to partners regarding marketing efforts through product promotion and distribution, both directly and via social media to consumers.  It is hoped that the impact obtained by the community after this activity will increase the income of the partner group and be able to facilitate the development of partner businesses and then provide a multiplier effect for similar businesses.